REGULATION OF BLOOD PRESSURE, APPETITE AND GLUCOSE BY LEPTIN AFTER INACTIVATION OF INSULIN RECEPTOR SUBSTRATE 2 (IRS2) SIGNALING IN THE ENTIRE BRAIN OR IN POMC NEURONS - do Carmo, Jussara M. (Hypertension, 2015)
Insulin receptor substrate 2 (IRS2) is one of three major leptin receptor signaling pathways, but its role in mediating the chronic effects of leptin on blood pressure, food intake and glucose regulation is unclear. We tested if genetic inactivation of IRS2 in the entire brain (IRS2/Nestin-cre mice) or specifically in proopiomelanocortin (POMC) neurons (IRS2/POMC-cre mice) attenuates the chronic cardiovascular, metabolic and antidiabetic effects of leptin. Mice were instrumented with telemetry probes for measurement of blood pressure (BP) and heart rate (HR) and with venous catheters for intravenous infusions. After a 5-day control period, mice received leptin infusion (2 µg/kg/min) for 7 days. Compared to control IRS2(flox/flox) mice, IRS2/POMC-cre mice had similar body weight and food intake (33±1 vs. 35±1g and 3.6±0.5 vs. 3.8±0.2 g/day) but higher MAP and HR (110±2 vs. 102±2 mmHg and 641±9 vs. 616±5 bpm). IRS2/Nestin-cre mice were heavier (38±2 g), slightly hyperphagic (4.5±1.0 g/day), and had higher MAP and HR (108±2 mmHg and 659±9 bpm) compared to control mice. Leptin infusion gradually increased MAP despite decreasing food intake by 31% in IRS2(flox/flox) as well as in Nestin-cre control mice. In contrast, leptin infusion did not change MAP in IRS2/Nestin-cre or IRS2/POMC-cre mice. The anorexic and antidiabetic effects of leptin, however, were similar in all 3 groups. These results indicate that IRS2 signaling in the CNS, and particularly in POMC neurons, is essential for the chronic actions of leptin to raise MAP but not for its anorexic or antidiabetic effects.